A 6-Country Collaborative Quality Improvement Initiative to Improve Nutrition and Decrease Mother-to-Child Transmission of HIV in Mother–Infant Pairs. (26th June 2019) - Barker, Pierre; Quick, Timothy; Agins, Bruce; Rollins, Nigel; Sint, Tin Tin; Stern, Amy F.
Despite advances in coverage and quality of prevention of mother-to-child transmission (PMTCT) programs, infant protection from postnatal HIV infection remains an issue in high HIV-burdened countries. We designed a quality improvement (QI) intervention—the Partnership for HIV-Free Survival (PHFS)—to improve infant survival. PHFS convened leaders in 6 sub-Saharan African nations to discover together the best strategies for implementing and scaling up existing PMTCT protocols to ensure optimal health of mother–baby pairs and HIV-free infant survival. We used 3 core technical components—rapid adaptive design, collaborative learning, and scale-up/sustainability designs—to test strategies for accelerating effective PMTCT programming in complex, resource-poor settings. Learning generated included the need for increased ownership and codesign of improvement initiatives with Ministries of Health, better integration of initiatives into existing programs, and the need to sustain QI capability throughout the system. PHFS can serve as a design prototype for future global networks aiming to accelerate improvement, learning, and results.